190k views
2 votes
Solve the equation.

3 (x - 2)^2 - 8 = 5

1 Answer

6 votes

Answer:

Explanation:

3(x-2)(x-2)-8=5

3[x^2-4x+4]-8-5=0

3x^2-12x+12-13=0

3x^2-12x-1=0

use the quadratic formula to find x { -b+-sqrt(b^2-4ac) } / 2a

where a =3 , b=-12 and c =-1 from our equation above

{ -(-12)+- sqrt[ (-12)^2 - 4(3)(-1) ] } / [2(3)]

{ 12 +- sqrt [ 144 + 12 ] } / 6

{ 12 +- sqrt (156) } / 6

2 +- {sqrt ( 4 *13) } / 6

2 +- { 2 sqrt (13) } /6

2 +- sqrt (13) /3

there you go :)

User Andy Theos
by
5.2k points